The ectonucleotidases CD39 and CD73 on T cells: The new pillar of hematological malignancy - Jiang, Xuan; Wu, Xiaofang; Xiao, Yuxi; Wang, Penglin; Zheng, Jiamian; Wu, Xiuli; Jin, Zhenyi (Frontiers in Immunology, 2023)
Hematological malignancy develops and applies various mechanisms to induce immune escape in part through an immunosuppressive microenvironment. Adenosine is an immunosuppressive metabolite produced at high levels within the tumor microenvironment (TME). Adenosine signaling through the A2A receptor expressed on immune cells such as T cells potently dampens immune responses. Extracellular adenosine generated by ectonucleoside triphosphate diphosphohydrolase-1 (CD39) and ecto-5’-nucleotidase (CD73) molecules is a newly recognized “immune checkpoint mediator” and leads to the identification of immunosuppressive adenosine as an essential regulator in hematological malignancies. In this review, we first provide an overview of the detailed distribution and function of CD39 and CD73 ectoenzymes in the TME and the effects of CD39 and CD73 inhibition in preclinical data in hematological malignancies, which provides insights into potential clinical application for immunotherapy.